Production and characterization of probiotic jelly candy containing Bacillus species - Kahraman, Burcu; Korkmaz, Kader; Dastan, Dilara; Toker, Omer Said; Dertli, Enes; Arici, Muhammet (SPRINGER, 2023)
In this study, probiotic soft jelly candy was developed using Bacillus coagulans, Bacillus clausii and Bacillus subtilis as probiotics and the rheological, textural, microbiological and sensory characteristics of jellies were determined. In terms of probiotic features, the viability and in vitro gastrointestinal tract (GIT) durability of probiotics were determined during 3 months of storage. No alteration in the physicochemical properties of the soft candies was observed with the usage of probiotics (p > 0.05) in comparison to the control samples. Utilization of the probiotic strains resulted in the increment of the total phenolic content and antioxidant capacities of soft candies. The flow behavior characteristics of the soft candies did not change with the addition of probiotics and they showed similar viscosity values. Jelly candies (P1, P2, EG and BB2) containing strains of Bacillus subtilis, Bacillus coagulans and Bacillus clausii preserved their probiotic properties until the end of the 90th day as the Bacillus numbers were higher than 6 log cfu/g. In the in vitro GIT test, the survival rate of Bacillus strains was over 90.36% at the end of the storage period. The produced probiotic jelly candies presented desired sensorial acceptability. These findings revealed that using of probiotic Bacillus strains is excellent alternative for production of functional confectionery.
Keywords: Bacillus probiotics; Probiotic soft jelly candy; In vitro gastrointestinal tract durability; DUCK FEET GELATIN; LACTOBACILLUS-ACIDOPHILUS; POULTRY GELATIN; SURVIVAL; VIABILITY; BACTERIA; TEXTURE; Food Science & Technology